Structural Basis of the Negative Allosteric Modulation of 5-BDBD at Human P2X4 Receptors - Bidula, Stefan; Nadzirin, Izzuddin Bin; Cominetti, Marco; Hickey, Harry; Cullum, Sean A.; Searcey, Mark; Schmid, Ralf; Fountain, Samuel J. (Molecular pharmacology, 2022)
The P2X4 receptor is a ligand-gated ion channel activated by extracellular ATP. P2X4 activity is associated with neuropathic pain, vasodilation, and pulmonary secretion and is therefore of therapeutic interest. The structure-activity relationship of P2X4 antagonists is poorly understood. Here we elucidate the structure-activity of 5-(3-bromophenyl)-1,3-dihydro-2H-benzofuro[3,2-e]-1,4-diazepin-2-one (5-BDBD) at human P2X4 by combining pharmacology, electrophysiology, molecular modeling, and medicinal chemistry. 5-BDBD antagonized P2X4 in a noncompetitive manner but lacked effect at human P2X2. Molecular modeling and site-directed mutagenesis suggested an allosteric binding site for 5-BDBD located between two subunits in the body region of P2X4, with M109, F178, Y300, and I312 on one subunit and R301 on the neighboring subunit as key residues involved in antagonist binding. The bromine group of 5-BDBD was redundant for the antagonist activity of 5-BDBD, although an interaction between the carbonyl group of 5-BDBD and R301 in P2X4 was associated with 5-BDBD activity. 5-BDBD could inhibit the closed channel but poorly inhibited the channel in the open/desensitizing state. We hypothesize that this is due to constriction of the allosteric site after transition from closed to open channel state. We propose that M109, F178, Y300, R301, and I312 are key residues for 5-BDBD binding; provide a structural explanation of how they contribute to 5-BDBD antagonism; and highlight that the limited action of 5-BDBD on open versus closed channels is due to a conformational change in the allosteric site. Activity of P2X4 receptor is associated with neuropathic pain, inflammation, and vasodilatation. Molecular information regarding small-molecule interaction with P2X4 is very limited. Here, this study provides a structural explanation for the action of the small-molecule antagonist 5-BDBD at the human P2X4 receptor.